Savings goal calendars as soft commitment devices: Evidence from small business owners in Uganda - Antonia Grohmann; Tabea Lakemann; Helke Seitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
This study examines the effect of a soft commitment device in the form of a savings goal calendar on savings for small business owners in Kampala, Uganda. We run a randomized controlled trial (RCT) under which the treatment group receives a calendar designed to set savings goals and to make a plan to reach this goal. The control group is given a plain calendar. We find no average effect on savings, but show that present-biased individuals save more when given the calendar. Further examinations indicate that present-biased individuals are more likely to use the calendar, suggesting that, in line with theory, present-biased individuals have a demand.
Keywords: O12; D14; D22; C93; 330; Soft Commitment; Savings; Time Preferences; Small Business Growth